Anticipatory sensitization to repeated stressors: The role of initial cortisol reactivity and meditation/emotion skills training. (February 2015) - Turan, Bulent; Foltz, Carol; Cavanagh, James F.; Alan Wallace, B.; Cullen, Margaret; Rosenberg, Erika L.; Jennings, Patricia A.; Ekman, Paul; Kemeny, Margaret E.
Highlights: Anticipatory cortisol levels can progressively increase before subsequent exposures. This is called progressive anticipatory sensitization of the cortisol response. Cortisol response to first stressor predicts progressive anticipatory sensitization. This may be a mechanism for the translation of short-to-long-term stress reactions. Emotional/meditation training reduces this progressive anticipatory sensitization. Summary: Anticipation may play a role in shaping biological reactions to repeated stressors—a common feature of modern life. We aimed to demonstrate that: (a) individuals who display a larger cortisol response to an initial stressor exhibit progressive anticipatory sensitization, showing progressively higher cortisol levels before subsequent exposures, and (b) attention/emotional skills training can reduce the magnitude of this effect on progressive anticipatory sensitization. Female school teachers ( N  = 76) were randomly assigned to attention/emotion skills and meditation training or to a control group. Participants completed 3 separate Trier Social Stress Tests (TSST): at baseline (Session 1), post-training (Session 2), and five months post (Session 3). Each TSST session included preparing and delivering a speech and performing an arithmetic task in front of critical evaluators. In each session participants' salivary cortisol levels were determined before and after the stressor. Control participants with larger cortisol reactivity to the first stressor showed increasing anticipatory (pre-stressor) cortisol levels with each successive stressor exposure (TSST session)—suggesting progressive anticipatory sensitization. Yet this association was absent in the training group. Supplementary analyses indicated that these findings occurred in the absence of group differences in cortisol reactivity. Findings suggest that the stress response can undergo progressive anticipatory sensitization, which may be modulated by attention/emotion-related processes. An important implication of the construct of progressive anticipatory sensitization is a possible self-perpetuating effect of stress reactions, providing a candidate mechanism for the translation of short-to-long-term stress reactions.